The Effect of the Plickers Application on Fourth-Grade Students’ Learning Motivation in Learning Integrated Themes - Arzfi, Bima Prakarsa; Yulianti, Niki; Desyandri, Desyandri; Irdamurni, Irdamurni (Universitas Pahlawan Tuanku Tambusai, 2022)
The Plickers app is an online learning assessment technology that uses smartphones and coded cards. Using this app it only takes 3-5 minutes to scan the card and get instant results. This study aims to determine the motivation of students in using the application. Plickers Application. This is Field Research. This research was conducted at SDN 33 Sawahan in the even period of 2021/2022. The subjects of this study were 18 fifth grade elementary school students learning comprehensive themes. Data was obtained by distributing questionnaires. Data analysis is descriptive and qualitative. The results showed that overall, 75% of students were motivated by: 1) 87% interested, 2) 85% benefited, 3) 74% felt confident, 4) 83% satisfied with the Plickers application. The results of this study can be concluded that Class V students respond positively to the use of the Plickers application for integrated thematic learning in elementary schools.